Pemanfaatan Legenda Kota Kudus untuk Meningkatkan Literasi Siswa Sekolah Dasar - Nandita Camelia Putri; Nabila Nor Isnaini; Fena Marlena; Luthfa Nugraheni (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Kudus City, which is rich in history and culture, has various legends that can be used as interesting learning resources. The purpose of this study was to determine the use of legends in improving elementary school students' literacy with the method used in this study is the Systematic Literacy Review (SLR). The use of sacred urban legends in learning can improve students' reading and improve their understanding of local cultural and historical values. In addition, this activity encourages students to get discussions and creative activities such as storytelling and art. Therefore, using legends as teaching materials not only improves literacy, but also builds a sense of love for local culture. This study recommends the integration of sacred urban legends into the elementary school curriculum as an effort to improve the quality of education and conservation of local culture. The results of this study indicate that the use of legends to help elementary school students become more literate is a successful strategy